Athleticogenomics and elite athletes: a review of the state of the art and a possible relationship with inflammatory response (Italian Journal of Public Health, 2011)
Background: Recent research in athleticogenomics has begun to reveal how particular genetic polymorphismsmay influence athletic status and confer an individual predisposition for better sports performances. Thisis of particular interest for elite athletes because it could help to assess an athlete’s potential, to enhancespecific training protocols for selected performances, to monitor the individual response to training load andrecovery and, finally, aid in the prevention of accidents.Methods: Using a topics search in the PubMed database, the search strategy included studies examiningthe relationship between the presence of polymorphisms in genes influencing selected physiologicalparameters and the elite athletic status. English written case (elite athletes) -control (general population)studies were selected.Results: 26 research articles concerning polymorphic genes involved in muscle physiology, cell respiratoryfunction, substrate supply and inflammatory response, significantly associated with a predisposition of eliteathletes for sports respect to their control counterparts were registered. The majority of the included genesare functionally linked but the gene involved in inflammatory responses and represents the first evidence ofan association between this gene polymorphism and elite athletic status.Conclusions: The identification of these polymorphisms could be potentially useful to evaluate an individual’spotential for elite sports disciplines. Moreover, as recently observed for the interleukin-1 receptor antagonist(IL-1RN) polymorphism, since there are genetic variants having a relevant role not only in sports medicine, butalso in the development of medical disorders, their study could help to better understand how a particularpolymorphism could influence the pathogenesis of a specific gene related disease.
Keywords: athleticogenomics; athletes; inflammatory response; review